PENILAIAN TINGKAT KEBAHAGIAAN MASYARAKAT KAMPUNG KOTA (STUDI KASUS KAWASAN PERMUKIMAN KAMPUNG BRAGA BANDUNG) - Sally Indah Nurdyawati; Holi Bina Wijaya (TATALOKA, 2018)
The measurement of happiness index in Indonesia was conducted by Badan Pusat Statistik (BPS) was first released in 2013 based on the result of study and representation of national level estimation. The approach taken is a life satisfaction, in which life satisfaction is believed to reflect the level of happiness. The city of Bandung is one of the cities that initiated the measurement of happiness index in Indonesia. Kampung Braga is one of Kampung Kota that still maintain its existence in the middle of the urban development. The neighborhood of Kampung Braga is considered as slum area and the buildings within break the river border line. According to  than phenomena, the research question comes up, "How big is the level of happiness Kampung Braga neighborhood?". Variables used ini this research consist of happiness and spatial variables. The analysis used is descriptive quantitative by weighting and scoring on each variable. Based on the results, the happiness index of Kampung Braga neighborhood is 0.978 which belongs to the category of very happy. In forming proccess of happiness, the affective component contribution is relatively balanced with the cognitive. Spatially, people in RW 04 and RW 08 tend to be happier. This study proves that the people of Kampung Braga have the ability to adapt to the urban environment.